Non-Labeling Diagnostic Assessment from a Human Dignity Perspective: Implications for Students’ Academic and Character Development - Tutughamiarso, Maya Oktavia; Triwiyanto, Wahyudi (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyse how the results of the Middle Years Information System (MidYIS) initial assessment can be interpreted and utilised pedagogically as a non-labelling assessment to support students’ academic and character development. A descriptive quantitative approach was used in this study, with a cross-sectional design, involving all 10th-grade students (n=35) at a private Christian high school in an urban Indonesian context as the sample, using a total sampling technique. Data were obtained from MidYIS Standard Age Scores (mean = 100, SD = 15) across six cognitive domains. The data analysis techniques in this study employed descriptive statistics and inferential statistical tests. The findings reveal significant cross-domain variation. Mathematics and Non-Verbal Reasoning demonstrate strong performance, with 45.7% of students in the Well Above to Far Above categories. In comparison, Perceptual Speed and Accuracy is the strongest domain (65.7% Above Average or higher). In contrast, Vocabulary shows greater dispersion, with 34.3% in the Below to Far Below categories. The Overall Ability mean (≈105.67) is slightly above the international benchmark, yet substantial intra-individual differences are evident, including cases of high mathematical ability alongside lower verbal performance. These results demonstrate that cognitive profiles are multidimensional and that a single ability label constitutes a scientific fallacy. MidYIS should therefore function as a reflective tool for differentiated learning rather than a predictive or labelling instrument, supporting educational practices grounded in assessment for learning and respect for human dignity.